2021
DOI: 10.1021/acsnano.0c10634
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Harmonophores for Targeted High-Resolution In Vivo Tumor Imaging

Abstract: Optical imaging probes have played a major role in detecting and monitoring a variety of diseases. In particular, nonlinear optical imaging probes, such as second harmonic generating (SHG) nanoprobes, hold great promise as clinical contrast agents, as they can be imaged with little background signal and unmatched long-term photostability. As their chemical composition often includes transition metals, the use of inorganic SHG nanoprobes can raise long-term health concerns. Ideally, contrast agents for biomedic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In the case of SHG (9), two photons with the same energy interact with a non-linear material and are effectively combined via virtual energy states to generate a new photon with twice the energy of the initial photons. Most TPEF and SHG biomedical applications exploit endogenous properties of tissues (10), but applications that involve labeling with fluorescence dyes (11) and harmonophores (12) have also been reported. Among the most discussed TPEF sources of endogenous contrast are metabolic substrates (e.g., NADH and FAD), structural proteins (e.g., elastin and keratin), lipofuscins, and melanin.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of SHG (9), two photons with the same energy interact with a non-linear material and are effectively combined via virtual energy states to generate a new photon with twice the energy of the initial photons. Most TPEF and SHG biomedical applications exploit endogenous properties of tissues (10), but applications that involve labeling with fluorescence dyes (11) and harmonophores (12) have also been reported. Among the most discussed TPEF sources of endogenous contrast are metabolic substrates (e.g., NADH and FAD), structural proteins (e.g., elastin and keratin), lipofuscins, and melanin.…”
Section: Introductionmentioning
confidence: 99%
“…135 Periklis Pantazis et al demonstrated the above-mentioned advantages of nanoprobes generating second harmonics if used for in vivo imaging based on inorganic SHG nanoprobes, which can avoid many limitations of conventional fluorescent probes. 136 However, Periklis Pantazis' team had concerns about their long-term health, causing them to develop biodegradable harmonophores, which consisted of polymer-encapsulated, self-assembled peptides that produce strong SHG signals comparable to inorganic SHG nanoprobes (Fig. 23B).…”
Section: Applications Of Piezoelectric Nano-biomaterials In Diagnosis...mentioning
confidence: 99%
“…Copyright 2010, National Academy of Sciences. (B) Synthesis process of bioharmonophores and imaging targeting single cancer cells in vivo 136. Copyright 2021, the American Chemical Society.…”
mentioning
confidence: 99%
“…The stain was removed from the tooth surface after 2000 cycles [80] Ferroelectric materials Biosensing LV-like silver nanowires Real-time monitoring breath, heartbeat pulse, and swallowing [177] PVDF/HHE OPNS Capture micropressure changes at the outside of cardiovascular [95] rGO/PVDF Monitoring arterial pulse pressure and temperature simultaneously [91] PZT nanoribbons Measured the mechanical deformations brought on by electrical excitations in neuronal cells [84] Bioimaging and phototherapy Bioharmonophores Detect single cancer cells in zebrafish embryos [175] SHG nanoprobes In vivo imaging 179]…”
Section: Batio 3 Nanowiresmentioning
confidence: 99%
“…Ideally, biomedical imaging probes used in vivo should be biodegradable without any long-term toxic effects from byproducts. Recently, Sonay et al [175] created a biodegradable SHG nanoprobe from FFF peptide nanoprobes. Researchers have found an increase in the accumulation of p32 peptide targeting biologically harmless carriers within a single cancer cell at the tumor site of the entire zebrafish embryo, improving labeling efficiency and sensitivity (Figure 12d).…”
Section: Bioimaging and Phototherapymentioning
confidence: 99%